The rheumatoid arthritis impact of disease (RAID) score in telemedicine management of rheumatoid arthritis - Taylor, PC (Journal of Rheumatology, 2024)
The sudden and unanticipated emergence of SARS-Cov-2 at the beginning of the present decade, associated with high morbidity and mortality among people infected, prompted the rapid emergence of telemedicine approaches for the management of patients with rheumatoid arthritis (RA). The rationale was to limit the likelihood for viral contagion in a hospital outpatient setting for people rendered potentially more vulnerable by the immunosuppressive nature of many of the pharmacological interventions in the treatment armamentarium.